In-depth study of single photon time resolution for the Philips digital silicon photomultiplier. (9th June 2016) - Liu, Z.; Gundacker, S.; Pizzichemi, M.; Ghezzi, A.; Auffray, E.; Lecoq, P.; Paganoni, M.
Abstract: The digital silicon photomultiplier (SiPM) has been commercialised by Philips as an innovative technology compared to analog silicon photomultiplier devices. The Philips digital SiPM, has a pair of time to digital converters (TDCs) connected to 12800 single photon avalanche diodes (SPADs). Detailed measurements were performed to understand the low photon time response of the Philips digital SiPM. The single photon time resolution (SPTR) of every single SPAD in a pixel consisting of 3200 SPADs was measured and an average value of 85 ps full width at half maximum (FWHM) was observed. Each SPAD sends the signal to the TDC with different signal propagation time, resulting in a so called trigger network skew. This distribution of the trigger network skew for a pixel (3200 SPADs) has been measured and a variation of 50 ps FWHM was extracted. The SPTR of the whole pixel is the combination of SPAD jitter, trigger network skew, and the SPAD non-uniformity. The SPTR of a complete pixel was 103 ps FWHM at 3.3 V above breakdown voltage. Further, the effect of the crosstalk at a low photon level has been studied, with the two photon time resolution degrading if the events are a combination of detected (true) photons and crosstalk events. Finally, the time response to multiple photons was investigated.